Gray After Dark - Ihli, Noelle W. ([United States] : Dynamite Books, 2024)
A merciless wilderness. A harrowing attack. A desperate escape. When a tragic accident sidelines Mileys dreams of Olympic gold, she takes a summer job at a mountain guest lodge. The Frank Church Wilderness is remote, but its the perfect place to train and recover. Local lore about a staffer who died years ago doesnt scare her. But it should. Mileys plans take a terrifying detour when shes abducted during a morning run. Held captive in a desolate off-grid cabin, shell have to use her athletic prowess, cunning mind, and courage to survive. But as the nightmare at the cabin escalates, Miley is forced to form an unlikely alliance and attempt a risky escape. Can she outwit her captors and survive the wilderness before its too late? Inspired by true events, Gray After Dark is a pulse-pounding psychological thriller with a finale that will leave you breathless.
Keywords: Women -- Crimes against; Fiction; Women athletes -- Fiction; Survival -- Fiction; Kidnapping -- Fiction; Idaho -- Fiction; Thrillers (Fiction); Psychological fiction